Dose Planning Evaluation of Intensity-Modulated Proton Therapy (IMPT) Technique Based on In-House Dynamic Thorax Phantom - V. Vernanda; A. Azzi; S. A. Pawiro (Atom Indonesia, 2023)
One of the drawbacks of the Intensity Modulated Radiation Therapy (IMRT) technique is that the absorbed dose in healthy tissue is relatively high. Proton beam has characteristics that can compensate for these drawbacks. The Bragg peak characteristic of a proton beam allows the administration of high radiation doses to the target organ only. Non-Small Cell Lung Cancer (NSCLC) cases are located in the vicinity of many vital organs, so radiation doses that exceed a certain limit will have a significant impact on these organs. Proton is a heavy particle that exhibits interaction patterns with tissue heterogeneity that differ from that of photon. This study aims to determine the distribution of proton beam planning doses in the NSCLC cases with the Intensity Modulated Proton Therapy (IMPT) technique and compare its effectiveness with the IMRT technique. Treatment planning was done by using TPS Eclipse on the water phantom and on the in-house thorax dynamic phantom. The water phantom planning parameters used are one field at 0° and three fields at 45°, 135°, and 225°. In this study, a single, sum, and multiple field techniques on the in-house thorax dynamic phantom were used. The evaluation was performed by calculating Conformity Index (CI), Homogeneity Index (HI), and Gradient Index (GI) parameters for each treatment planning. As a result, a bit of difference in the CI the HI values are shown between IMPT and IMRT planning. The GI values of IMPT planning are in the range between 4.15-4.53, while the GI value of IMRT is 7.89. The histogram results of the planar dose distribution show that the IMPT treatment planning provides fewer off-target organ doses than the IMRT planning. Evaluation was also carried out on the    IMPT treatment planning of target organs in five areas of interest and four OAR positions. The evaluation results were then compared with the IMRT measurement data. As a result, the value of the point doses at the target organ      did not differ significantly. However, the absorbed dose with the IMPT technique at four OAR positions is nearly zero, which had a large difference compared to the IMRT technique.